e-Shopping Behavior: An Empirical Study of Malaysian Consumers - Baharin, Syaza Nabilah Kamal; Abd Aziz, Najdah Binti; Mahmud, Syahrul Hezrin (Journal of Economics and Behavioral Studies, 2024)
Malaysia’s e-commerce industry has grown tremendously, and many activities have been made online. One of the most common activities is online shopping or e-shopping. Online shopping behavior is the actions and decisions of customers when making purchases and completing transactions through Internet-based platforms. Consumer preference for online shopping is because it offers ease of buying or convenience, time-saving, price sensitive, anywhere-anytime, cost-effective, and other categories availability. Thus, this study investigated a few factors that affect Malaysian consumers’ online purchase behavior: information availability, social influence, and trust. The researcher used an online survey and a self-administered questionnaire to gather data on the phenomenon. Data were collected from 297 Malaysian respondents using convenience sampling and analyzed using IBM Statistical Package for the Social Sciences (SPSS) 26.0 version software. The results revealed that all independent variables (information availability, social influence, trust) had a significant positive relationship with the dependent variable (online shopping behavior). This study also proved that information availability was the most influential factor compared to other variables. It is hoped that this study will benefit Malaysian marketers as it focuses on the Malaysian context. This finding will also help e-retailers enhance their online sales by creating a strategy that could attract more customers as a concern for building profitable relationships.